2017
DOI: 10.21475/ajcs.17.11.12.pne665
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water supply and fluctuations on yield and quality of lemon balm (Melissa offici-nalis L.)

Abstract: The response of lemon balm (Melissa officinalis) on drought stress was investigated in a pot experiment in 2015-16. In treatment S1, plants grew in 40% saturation of soil water capacity (SWC) for six weeks. In treatment S2, the same level of water supply was used for three weeks, while the control plants received irrigation up to 70% SWC throughout the experimental period. In the second year, after the stress period, a 3 week re-hydration phase was also carried out. Growth, morphology, biomass, active componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…The findings of our study are confirmed by Németh et al [66], who suggested that short-term water shortages (up to three weeks) followed by rehydration does not affect the essential oil yield and only when water deficit is applied for six weeks are the effects on oil yield irreversible. In contrast to our study, Bonacina et al [1] suggested that salinity stress decreased essential oil yield with increasing salinity levels, while it increased the number of detected volatile compounds.…”
Section: Resultssupporting
confidence: 90%
“…The findings of our study are confirmed by Németh et al [66], who suggested that short-term water shortages (up to three weeks) followed by rehydration does not affect the essential oil yield and only when water deficit is applied for six weeks are the effects on oil yield irreversible. In contrast to our study, Bonacina et al [1] suggested that salinity stress decreased essential oil yield with increasing salinity levels, while it increased the number of detected volatile compounds.…”
Section: Resultssupporting
confidence: 90%